Impact of galcanezumab on total pain burden: findings from phase 3 randomized, double-blind, placebo-controlled studies in patients with episodic or chronic migraine (EVOLVE-1, EVOLVE-2, and REGAIN trials) - Ailani, Jessica; Andrews, J. Scott; Rettiganti, Mallikarjuna; Nicholson, Robert A. (Journal of headache and pain, 2020)
Background Focus on the frequency of migraine pain may undervalue the total burden of migraine as pain duration and severity may present unique, additive burden. A composite measure of total pain burden (TPB; frequency, severity, and duration) may provide a more comprehensive characterization of pain burden and treatment response in patients with episodic migraine (EM) or chronic migraine (CM). The impact of galcanezumab versus placebo on TPB among patients with EM or CM was analyzed. Methods Patients from randomized, double-blind, placebo-controlled episodic (two 6-month studies pooled) and chronic migraine (3-month) studies received once-monthly subcutaneous injection of galcanezumab 120 mg or placebo. A post hoc analysis of TPB for a given month was calculated as severity-weighted duration by multiplying duration (hours) and maximum pain severity (0 = none, 1 = mild, 2 = moderate, 3 = severe) of migraine for each day and summing these over the days in a month. Least square mean change from baseline in monthly TPB across Months 1–6 (EM, N = 444 galcanezumab, N = 894 placebo) and Months 1–3 (CM, N = 278 galcanezumab, N = 558 placebo) were compared using a mixed-model repeated measures model. Correlation of the Migraine Specific Quality of Life Questionnaire (MSQ) and Migraine Disability Assessment Scale (MIDAS) to TPB at baseline was assessed. Results At baseline, the duration of migraine on a given migraine headache day accounted for the greatest unique proportion of variability (EM, 57.4% and CM, 61.1%) to TPB after adjusting for frequency of migraine headache days and maximum pain severity. The decrease from baseline in monthly TPB was greater with galcanezumab than placebo for patients with EM (68.6 versus 36.2) and CM (102.6 versus 44.4). The average percent reduction of TPB from baseline was significantly greater with galcanezumab compared with placebo in patients with EM (50.8% versus 17.2%) and CM (29.7% versus 11.0%). In patients with EM and CM, TPB correlated with MSQ total score ( r = − 0.35 and r = − 0.37) and MIDAS ( r = 0.34 and r = 0.32). Conclusions Greater reduction in TPB was seen in patients with EM and CM treated with galcanezumab 120 mg once-monthly injection relative to placebo. Discussing TPB supports patient-centric conversations regarding treatment expectations when clinicians are evaluating options for migraine prevention. Trial registration ClinicalTrials.gov : # NCT02614183 (I5Q-MC-CGAG; EVOLVE-1), # NCT02614196 (I5Q-MC-CGAH; EVOLVE-2), and # NCT02614261 (I5Q-MC-CGAI; REGAIN) – all 3 trials were registered on 23 November 2015.